Architecture document management Applications Request the addition of raw materials on the CV. Zaneti 9 Using Administrative Workflow System - Saputra, Robby Cahyadi; Sutomo, Erwin; Wahyuningtyas, Nunuk (Jurnal Sistem Informasi Universitas Dinamika (JSIKA), 2016)
CV. Zaneti 9 is a construction company specialized in services of asphalting, street casting and making drains water. Management of document requests to add raw materials on the CV. Zanetti 9 still using paper documents. Based on the current administrative conditions, time required to recap of data requests takes 1-2 days. The Administration Also has long-time constraints on the approval of the addition of raw materials.Based on this problem , then made application management of document requestsÂ the addition of raw materials by applying administrative workflow system. This application applies the theory of Administrative workflow system to make sure process flow can be run well.It was concluded that this application has been able to accelerate the process of request for the addition of raw materials and also improves the performance of the process of creating the document recaps the addition of raw materials. This is seen in the time it takes to request additions raw materials to finished and also the time required to make the document recaps the addition of raw materials. At first it requires total time 36 hours to 26 minutes after use the application.